SURVEI MOTIVASI SISWA TUNARUNGU-WICARA TERHADAP PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SEKOLAH LUAR BIASA NEGERI BANGKINANG KOTA - Jeri Lorenza; Slamet Slamet; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research was conducted with the aim to find out more about the level of motivation of deaf students in learning physical education of sport and health in Public Special School of Bangkinang Kota. The problem found in this research in Public Special School of Bangkinang Kota, the implementation of physical education of sport and health education is carried out only on Saturdays and combines all students. The research was carried out in Public Special School of Bangkinang Kota, which was addressed at Letnan Boyak street, Bangkinang Kota, Kampar District. Conducted from January to Juli 2020. The population in this study were Deaf-Speech students in Public Special School of Bangkinang Kota. While the sampling technique used is saturated sampling, which uses all members of the population, if the population is relatively small, less than 30, that is, all deaf-speech students totaling 15. Based on the results of the study, the following conclusions can be drawn: 'as many as 53,3% or 8 deaf-speech students in Public Special School of Bangkinang Kota, have high levels of motivation towards learning physical education of sport and health, 40,0% or 6 deaf-speech students in the Medium category and 6,7% or 1 deaf-speech student in the Less category.Key Words: Motivation, Physical Education of Sport and Healt’s Learning